Participation: Optimising Outcomes in Childhood-Onset Neurodisability. Un livre paru en 2020 de C. Imms et D. Green - Gagné-Trudel, Sandrine (Revue Francophone de Recherche en Ergothérapie, 2020)
Sans résumé.